Application of Contrast Enhancement Bilateral Closing Tophat Otsu Thresholding Technique on Crack Images - K. S., Sim; Y. Y., Kho; C. P., Tso (2008)
This paper introduces the Contrast Enhancement Bilateral Closing Tophat Otsu Thresholding (CEBICTOT) technique to perform crack detection. This technique is based on the mathematical morphology and image filtering technique to extract the crack-like patterns. Mathematical morphology highlight the cracks clearly, and bilateral filtering, it moves noise from the image efficiently while preserving the edges. The CEBICTOT crack detection technique can be applied on concrete block surface images.